Treasury management and its influence on the liquidity of the Private University of Tacna, 2013-2014 - Llerena Talavera, Diana Karina (2017)
The present investigation had as objective to determine if the treasury management has influence in the liquidity of the Universidad Privada de Tacna, during the period 2013-2014. Pure investigation, with explanatory level, and with non-experimental and longitudinal design. The main actors of the management of the University fomd the study population. The instruments used were: a questionnaire designed to assess the percetion of the relationship between the management of the Treasury Department in th University´s liquidity and the documentary analysis guide to evaluate the management of the Treasury Department and the liquidity. According to the results, it was established that, at 95% confidence level, it is determined that the management of the Treasury Area influences the liquidity of the Private University of Tacna, in the period 2013-2014 (p:0.024)